Bukit Tagar sanitary landfill: commitment influence among general workers / Mohd Hazrul Naquib Abd. Yazid - Abd. Yazid, Mohd Hazrul Naquib (Faculty of Business and Management, 2009)
Employees in modern “learning” organizations are increasingly expected to display effort, motivation and initiative. The success of an organization depends not only on how the organization makes the most of human competences, but also how it stimulates commitment, together with a competent workforce, seems to be of decisive importance for an organization to be able to compete in quality and to go along with changes. Factors influence commitment such personal characteristics, job characteristics and structural characteristics have been identified in order to investigate whether or not these factors have a significant relationship with the commitment. The sample size for this study was 100 general workers who had any different background based on academic. Data was obtained using two methods, which were primary and secondary data. The Statistical Package for the social science (SPSS) version 14.0 has been used to summarize the data. Data analysis and interpretation are using frequency distribution, descriptive statistical and Pearson Correlation. The result indicate that level of commitment among the general workers toward Bukit Tagar Sanitary Landfill and need to be improve in order to achieve a high level of commitment. KUB Bejaya Enviro Sdn Bhd need to improve the level of commitment to all general workers in Bukit Tagar Sanitary Landfill such the general workers attitude especially. The conclusion of the study is the outcome of the survey analysis and findings. Based on findings, some recommendations have been suggested in order to help increase the element of commitment among general workers and for future research.